Direct Instruction Learning Strategy for Children with Mild and Moderate Intellectual Barriers to Reduce Maladaptive Behavior in the School Environment - Annisa Regina Anandari; Retno Pangestuti (al-Afkar, Journal For Islamic Studies, 2024)
In the field of education, the term "teaching strategies" is common. There are various teaching strategies available. When selecting and implementing these strategies, it is necessary to observe the learners to adjust to their needs, weaknesses, strengths, interests, talents, and abilities. This is particularly important for Children with Special Needs (CSN) who have intellectual disabilities. Children with intellectual disabilities tend to exhibit maladaptive behaviors because most of them do not understand what is good and what is bad, and they require guidance according to their classifications. In this disability, there are also three classifications: mild, moderate, and severe. This study is a qualitative research using a case study approach. The research was conducted at SLB BC Bina Insan Mandiri Mojolaban, with intellectually disabled children as the sample, using the direct introduction teaching strategy in all their learning activities, especially in Islamic Education.